SOSIALISASI HAK WARIS ISLAM BAGI PENGURUS DAN WARGA RW 010 KELURAHAN MADYOPURO KECAMATAN KEDUNGKANDANG MALANG - Muslim, Shohib; Chalim, Abdul; Fadloli, Fadloli; Setiawan, Ikhsan (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Training in the division of inheritance or the science of faraidh according to the KHI is the most important because this science is very rare in Muslim societies. This is due to the fact that it has a high degree of difficulty, especially for ordinary people, and it also becomes undesirable to talk about for fear of offending others if they are grieving. As a result, many Muslims do not understand this. Their lack of understanding can lead to quarrels and commotion in the house. There may even be bloodshed just because of fighting for inheritance. Thus, this community service activity is carried out. This is done because the community, consisting of residents and regional administrators, needs assistance to understand Islam in general. There are several activities that have been carried out, including inheritance science training according to KHI, discussion and question and answer, and mentoring aimed at providing solutions to the problem of inheritance distribution. Service activities are carried out through gradual mentoring of the chosen strategy in this activity using a combination of direct training methods, which include lectures, information discussions, and direct practice of calculating the distribution of inheritance. Weak legal awareness is overcome through the process of socialization, coaching, and inheritance law education. Where people admit that they lack a positive understanding of inheritance law. Some indicators of legal awareness include knowledge of legal statutes, knowledge of the content of statutes, views on statutes, and patterns of legal action